Management of Orbital Granulomatous Polyangiitis Presenting with Lacrimal Gland Involvement: Treatment of Subsequent Peripheral Ulcerative Keratitis, Anterior Uveitis, and Exudative Retinal Detachment in a Challenging Case - Murat Oklar; Elif Sarı; Hatice Selen Kanar; Hikmet Süslü; Tufan Çiftçi; Mehmet Engin Tezcan (Türk Oftalmoloji Dergisi)
This case report discusses a case of granulomatosis with polyangiitis (GPA) initially presenting with lacrimal gland involvement and subsequently developing additional features. GPA is a disease known for inflammation in the respiratory tract and kidneys. A 63-year-old male patient presented with a mass, swelling, and ptosis in the right upper eyelid. The patient was referred to us when his symptoms had persisted and worsened despite topical and oral antibiotic therapy administered at another center. Based on clinical and laboratory findings from evaluation and consultations, GPA was diagnosed and confirmed by biopsy. The patient initially presented with necrotizing scleritis and later developed peripheral ulcerative keratitis and anterior uveitis, which regressed under cyclophosphamide treatment but progressed to exudative retinal detachment due to orbital involvement. Clinical remission was achieved after adding rituximab therapy. Presentation with lacrimal gland involvement may serve as an initial manifestation of locally aggressive orbital and adnexal GPA, which can exhibit variable clinical features. Rapid diagnosis and aggressive treatment are critical for preserving vision and preventing complications in patients with GPA.